"Food System Mapping in Kanyanya (Kampala)" - Workshop Report. - Linderhof, V.; Dijkxhoorn, Y.; Fongar, A.; Onyango, J.; Nalweyiso, M. (2019)
Food value chains are part of the systemic drivers of urban food and nutrition security. An important part of these value chains are the various informal small actors. These include producers, transporters, processors and retailers. One of the main objectives of the NOURICITY project is to initiate and to implement partnership agreements between different local, national and international stakeholders to improve the urban food system. Therefore, we conducted a workshop as indicated by Work Package 1 of the NOURICITY project. This workshop aims to map the stakeholders of the food system in Kampala and to map the food flows in one of the parishes in Kampala. The parish selected was Kanyanya (Kawempe division). The workshop consisted of two days with two groups of people: the first day for parish representatives and the second day for Kampala and national representatives.